Workshop Worksheet Berbasis Budaya bagi Guru MI Jami’atul Qamar Tanjung Morawa - Sukmawarti; Hidayat; Lili Amelia Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Creative thinking, critical thinking, communicating, and collaborating are 21st century skills needed in the era of the industrial revolution 4.0. Skills are not just knowledge abilities, but are more about showing skills in problem solving using creative, critical thinking, communication, and collaboration. Based on initial observations at MI Jami'atul Qamar Tanjung Morawa, it was found that the problems faced by teachers in learning, including not much information related to the development of 21st century skills, teachers rarely use worksheets as student activity sheets, misconceptions of worksheets as learning tools, lack of teacher skills designing worksheets that contain student activities oriented to real world problems. In response to these problems, activities were carried out to overcome them through Community Service Program activities in the form of a culture-based worksheet design workshop. This program is implemented with 2 methods, namely workshops and mentoring. The workshop was carried out in 3 stages, namely tutorial, training, and simulation (peer demonstration). Meanwhile, assistance is carried out through 3 stages, namely implementation, evaluation and reflection. The output of this service activity is a culture-based worksheet product, and 85% of the achievement of improving teacher skills in designing and implementing culture-based worksheets in mathematics learning.